THE USE OF INNOVATIVE APPROACH TECHNIQUES IN IMPROVING THE PEDAGOGICAL SKILLS OF TEACHERS - Jumayeva Gulnora Tursunpo`latovna (Scholar Express Journal, 2021)
This article deals with the use of innovative approach techniques in improving the pedagogical skills of teachers. Professional pedagogical culture is an indispensable quality of the teaching person who has a pedagogical profession, who designs his general culture. This is the synthesis of high professionalism and internal characteristics of the teacher, the mastery of teaching methods and the availability of cultural and creative abilities. This is a measure of creative assimilation and transformation of the experience accumulated by mankind. A teacher with a pedagogical culture, a well-developed pedagogical mind and consciousness, a creative potential
Keywords: Culture, important, approach, skill, profession